ANALISIS PENGARUH MARKETING MIX 7P TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada CV. Karya Apik MAN 3 JOMBANG) - Muhyiddin Zainul Arifin; Ika Maya Rosyidah; Nia Aprilia Bisari (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this study was to analyze the effect of product, price, place, promotion, process, people, physical evidence on purchasing decisions on CV. Great Work. This type of research is quantitative research with survey research methods. In collecting data using non-probability sampling technique. The population of this study were respondents on CV. Nice work, so the sample in this study amounted to 82 respondents. The testing technique of this research instrument is validity and reliability test, while data analysis is obtained using Classical Assumption Test, Multiple Linear Regression and Correlation Coefficient Test using F test (simultaneous test), T test (partial test). The results of research and data processing show that the seven independent variables are product, price, place, promotion, process, people, physical evidence of purchasing decisions on CV. Great Work. The results of the correlation coefficient test show that the R value is 0.990, meaning that products, prices, places, promotions, processes, people, physical evidence together have a very strong relationship to purchasing decisions. While the results of the coefficient of determination test show that the value of R2 is 0.978, then the value of R2 <1 means 97.8% of employee performance at CV. Apik's work is influenced by product, price, place, promotion, process, people, physical evidence. While the rest (2.2%) is influenced by other variables outside the study.